Problematika Perkawinan Beda Usia Pada Masyarakat Kecamatan Cina Perspektif Hukum Islam - Zakfah, Misnawati; Sarina, Sarina (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This research aims to determine the perspective of Islamic law regarding age difference issues in the Chinese District community and efforts to overcome the problem of age difference marriages in the Chinese District community. Research data was obtained by conducting qualitative field research using observation, documentation and direct interview data collection techniques with the community in Cina District. The research approach used is a normative theological and sociological approach. The results of the research show that the people of China District have varying views regarding age-gap marriage, where some support it on the grounds that age is not the only indicator of maturity and success in marriage, while others disagree because of the social stigma attached. From the perspective of Islamic law, this kind of marriage is considered valid as long as it meets the specified conditions and harmony, although the couple needs to overcome challenges arising from the age difference. The efforts made by the people of China District in overcoming the problems that arise in age-gap marriages are compromising on the expectations of each partner, looking for similar interests in each other, ensuring that values, morals and life goals are in accordance with each other, seeking social support, planning problem solving, using coping strategies in solving problems.